2012
DOI: 10.1208/s12249-012-9909-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Agglomerate Abrasion in a Tumbling Blender by Using the Stokes Number Approach

Abstract: Abstract. Removal of microcrystalline cellulose agglomerates in a dry-mixing system (lactose, 100 M) predominantly occurs via abrasion. The agglomerate abrasion rate potential is estimated by the Stokes abrasion (St Abr ) number of the system. The St Abr number equals the ratio between the kinetic energy density of the moving powder bed and the work of fracture of the agglomerate. Basically, the St Abr number concept describes the blending condition of the dry-mixing system. The concept has been applied to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Breakage of agglomerates is governed by the balance (i.e., ratio) of the kinetic energy of the material (source for bond breakage) and the work needed to break the cohesive/adhesive bonds. The Stokes number and the ratio of the impact energy to the work done by the adhesive force, which essentially characterizes this balance, have been found to control agglomerate abrasion and breakage. Based on a similar idea, for the breakage of wet flexible agglomerates in the current study, the Weber number was used to characterize the ratio of the fiber kinetic energy compared to the work done to stretch a liquid bridge bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breakage of agglomerates is governed by the balance (i.e., ratio) of the kinetic energy of the material (source for bond breakage) and the work needed to break the cohesive/adhesive bonds. The Stokes number and the ratio of the impact energy to the work done by the adhesive force, which essentially characterizes this balance, have been found to control agglomerate abrasion and breakage. Based on a similar idea, for the breakage of wet flexible agglomerates in the current study, the Weber number was used to characterize the ratio of the fiber kinetic energy compared to the work done to stretch a liquid bridge bond.…”
Section: Resultsmentioning
confidence: 99%
“…The modified Weber number is proportional to the square of impact velocity, and is inversely proportional to the liquid surface tension and the rupture distance. Previous work reports that the abrasion and breakage of agglomerates is characterized by the Stokes number of fracture, which is proportional to the square of impact velocity, v , and is inversely proportional to the square of the material yield strength, σ Y : St=ρbv2EσY2, in which ρ b is the bulk density and E is the Young's modulus of the particles. Both the present modified Weber number and the previous Stokes number describe the ratio between the impact kinetic energy and the work of fracture of the agglomerate.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the mixer rotation speed and the mixer size on abrasion were consistent with experiments . In addition, it was found that the Stoke number, defined as the ratio between the kinetic energy density of a powder bed and work of fracture of an agglomerate, was proportional to the abrasion rate, as observed in the experiments …”
Section: Introductionmentioning
confidence: 99%